(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Intro Good service is one of the most essential in the Food and beverages industry, and Technology is unquestionably one of the factors that contribute to high-quality service; without proper service, there would be no consumers, and the business will not be able to achieve its goal. For this reason, it’s critical that your service system is of high quality and meets the demands and preferences of your target audience. Therefore, the purpose of this study is to collect all relevant data on the service system and determine what is the effect of enhancement in the service system on customers. In addition, the researchers also aim to provide reliable information about the new modern service system that will help the current generation and future researchers. The result of this study reveals that the majority of the customers from selected fast food chains at Sm Fairview are evaluated as "agree" in terms of Taking Orders, Contactless Payment, Mobile Apps, and Digital Kitchen Board, but there are some variables that came out as the result "disagree" including the Lack of Priority Lanes, On-time Delivery of Foods, and The food ordered is accurate as what is on the menu board; this study’s findings shows the most problem encountered by the customers is the long wait for food delivery and the identicality of the menu board. The researchers recommend that every fast-food restaurant should install self-service kiosks to eliminate line-ups and improve customer service. Continue to expand priority lanes to guarantee that senior clients do not have to wait too long and that orders are processed quickly. When placing orders, using a coupon is more convenient and may result in more savings. In terms of the service they provide, clients should be informed that the expected time can alter when ordering online so that they do not have to wait too long and can plan when to expect their goods. Fast food establishments should accept e-wallets as payment because the bulk of this generation uses them. It is convenient because many older individuals lack knowledge about technology. When they find out how to use it, it is convenient since paying with an e-wallet ensures that they are charged the correct amount because some older people do not know or see the bill they have. Customers are also more likely to make a purchase when a fast-food restaurant’s menu is well-organized. It becomes more tempting with a comprehensible and attractive menu.